Determining Goods Delivery Priority for Transportation Service Companies Using SAW Method - Sumaizar Sumaizar; Kalvin Sinaga; Eko Deswin Siringo-ringo; Victor Marudut Mulia Siregar (Information Technology and Science (ITScience), 2021)
This research was conducted aiming to overcome the problem of the effectiveness of the delivery of goods by the Cendrawasi Expeditionary Company which at this time still does not use a decision support system approach. For the process of delivering goods to customers to be carried out effectively, a decision support system is designed that functions to determine the priority of goods to be delivered first. This problem is solved by designing a decision support system using the Simple Additive Weighting (SAW) method which serves to help the Cendrawasi Expeditionary company get recommendations for priority delivery of goods. The SAW method is very appropriate to be used as a decision support tool where in this study three alternative choices of goods that must be delivered first were obtained, namely plywood with a preference value of 99,6, mattress with a preference value of 83,55, and PVC pipes with a preference value of 79,35.